1971
DOI: 10.1210/jcem-32-1-59
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Free and Sulfate-Conjugated Neutral Steroids by the Human Testis. Effect of Administration of Human Chorionic Gonadotropin1

Abstract: Blood samples were obtained from the spermatic and peripheral veins of 8 males during an operation for inguinal hernia. Three of the subjects were treated with human chorionic gonadotropin (HCG) before collection of the samples. Neutral steroids in the fractions of free, mono-and disulfated compounds were identified and quantified, using gas-liquid chromatography and gas chromatography-mass spectrometry. In addition to testosterone, androstenedione and dehydroepiandrosterone, the following unconjugated neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
2

Year Published

1975
1975
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(35 citation statements)
references
References 17 publications
5
28
2
Order By: Relevance
“…An A-diol/T ratio of 0.2 in human spermatic venous blood has been found by Laatikainen et al (11). Such a ratio between these two steroids has also been recorded in the systemic blood circulation of normal men (18).…”
Section: Introductionmentioning
confidence: 65%
“…An A-diol/T ratio of 0.2 in human spermatic venous blood has been found by Laatikainen et al (11). Such a ratio between these two steroids has also been recorded in the systemic blood circulation of normal men (18).…”
Section: Introductionmentioning
confidence: 65%
“…Several steroids have been found to be secreted directly by the testes. In males approximately 40% of 17a-hydroxypregnenolone secretion is of testicular origin (35), and DHA, though mainly secreted by the adrenal, has also been found in the spermatic vein effluent of man (36). A5-androstene-Schneider, Genel, Bongiovanni, Goldman, and Rosenfield diol is the second most abundant steroid in spermatic vein plasma; the ratio of testosterone to DHA is 37:1, compared to 4: 1 for testosterone to A5-androstenediol (36).…”
Section: Resultsmentioning
confidence: 99%
“…In males approximately 40% of 17a-hydroxypregnenolone secretion is of testicular origin (35), and DHA, though mainly secreted by the adrenal, has also been found in the spermatic vein effluent of man (36). A5-androstene-Schneider, Genel, Bongiovanni, Goldman, and Rosenfield diol is the second most abundant steroid in spermatic vein plasma; the ratio of testosterone to DHA is 37:1, compared to 4: 1 for testosterone to A5-androstenediol (36). This latter ratio corresponds to that found in the peripheral plasma by Rosenfield and Otto (8) and confirmed by recent studies from two separate laboratories (37,38).…”
Section: Resultsmentioning
confidence: 99%
“…It has been known for a long time that the human testis is able to produce large amounts of steroid sulfates (Laatikainen et aL, 1971;Ruokonen et t al., 1972). More recent data have shown that these sulfoconjugates can be used as testicular androgen precursors and suggested that steroid sulfatase (STS) may act as a regulatory enzyme for the release of free androgens in humans (Bolton et al, 1985) and boars (Orava ef t aL, 1985).…”
Section: Introductionmentioning
confidence: 99%